Pemberdayaan Masyarakat dalam Memanfaatkan Wakaf Kawasan Desa Sumberbening, Bantur-Malang - Fitri Handayani, Ucik (Lembaga Penelitian, Pengembangan dan Pengabdian Kepada Masyarakat (LP3M), 2021)
The purpose of this service is to improve welfare through community and environmental empowerment in the use of wakaf. The empowerment activities that were carried out started from the observation of wakaf then continued with TPQ teacher training, traveling burdah and procurement of trash bins in various locations in the village of Sumberbening. The targets of this empowerment activity are the community of Sumberbening village, Islamic dormitory students, TPQ (informal institution for learning Al Qur’an) teachers and all members of community in Sumberbening. There are several stages in this program including planning, observing, implementing and evaluating. This empowerment activity is carried out in the process of the PKLI. The success of the implementation of this service is around 85%, because there are several work programs that have not been implemented. The program that has not been implemented is wakaf for reading books at the village. The evaluating of this service implementation is periodic assistance and increase partnerships with other parties that support the planned work program.